Echocardiographic Assessment of Cardiac Structure and Function of Centenarians: A Systematic Review - Andrea Sonaglioni; Gian Luigi Nicolosi; Giovanna Elsa Ute Muti-Schünemann; Alessio Polymeropoulos; Michele Lombardo; Paola Muti (Geriatrics)
Background: During the last two decades, a limited number of studies have provided echocardiographic details regarding the cardiac structure and function of individuals aged ≥100 years. These studies analyzed limited sample sizes of centenarians using different methodologies. The present systematic review was primarily designed to summarize the main findings of these studies and to examine the overall influence of extremely advanced age on cardiac structure and function. Methods: All echocardiographic studies that evaluated the cardiac structure and function in individuals aged ≥100 years, selected from the PubMed, Embase, Scopus and Cochrane Central Register of Controlled Trials (CENTRAL) databases, were included. There was no limitation on the time period. The risk of bias was assessed by using the National Institutes of Health (NIH) Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Results: A total of eight studies with 1340 centenarians [median age 101.4 years (IQR 101–103 years)] met the eligibility criteria and were analyzed. The centenarians were predominantly females [76.3% (IQR 60–85%)] with a small body surface area, long history of hypertension and slightly impaired renal functional reserve. The centenarian population showed a reduced burden of cardiovascular disease but an increased comorbidity burden, as assessed using the Charlson [median value 3.7 (IQR 1.8–5.5)] and Katz [median value 2.1 (IQR 1.1–3.1)] indexes. The echocardiographic findings comprised left ventricular (LV) concentric remodeling, with first-degree diastolic dysfunction [median E/A ratio 0.8 (IQR 0.7–0.9)], a moderate increase in LV filling pressure [median E/e’ ratio 16.8 (IQR 16.2–17)], normal LV systolic function [median left ventricular ejection fraction (LVEF) 60.9% (IQR 55–84%)] and mild-to-moderate pulmonary hypertension [median systolic pulmonary artery pressure 42.1 mmHg (IQR 37–54 mmHg)]. The pooled prevalence of LV systolic dysfunction (LVEF < 50%) was 15.8%. Moderate-to-severe valvular heart diseases were detected in less than one-third of the centenarians. Compared with the outpatient and in-home cohorts, hospitalized centenarians were less commonly females and were more likely to be affected by significant LV hypertrophy with a supra-normal LVEF, higher degrees of valvulopathies and impaired pulmonary hemodynamics. Conclusions: The evidence currently suggests that centenarians have typical LV concentric remodeling with increased myocardial stiffness and diastolic dysfunction, which predispose them to heart failure with a preserved ejection fraction (HFpEF). Cardioprotective treatment should be considered for personalized implementation and uptitration in this special population.